Global phenomena and social sciences : an interdisciplinary and comparative approach - Berge,Jean-Sylvestre (ed.).....[et al] (Switzerland : Springer nature, 2018)
This book offers new perspectives on global phenomena that play a major role in today's society and deeply shape the actions of individuals, organizations and nations. In a complex and rapidly changing environment, decision-makers need to gain a better understanding of global phenomena to adapt and to anticipate the evolution of the global context. The authors?ten renowned international scholars of anthropology, economics, law, management and political science?propose an interdisciplinary and comparative approach to social sciences.
Keywords: Globalization-Social aspects; International economic relations; Social sciences--Research